2023
DOI: 10.3390/cancers15123116
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Electrochemotherapy in Breast Cancer Patients of Different Receptor Status: The INSPECT Experience

Abstract: Electrochemotherapy has been proven to be an efficient treatment for cutaneous metastases of various cancers. Data on breast cancer (BC) patients with cutaneous metastases were retrieved from the INSPECT database. Patients were divided by their receptor status: HER2+, HR+ (ER/PgR+), and TN (triple negative). Groups were similar for histological subtype and location of the nodules. Most patients were previously treated with surgery/systemic therapy/radiotherapy. We found no differences in the three groups in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…There are various histologic types of breast cancer that differ in microscopic appearance and receptor expression, leading to differences in response to the treatment. Recently, a multicentric study investigating the efficacy of electrochemotherapy in breast cancer patients with different receptor statuses was published ( 54 ). The study demonstrated that electrochemotherapy is equally effective in the treatment of breast cancer metastases, regardless of receptor status.…”
Section: Electrochemotherapy In Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation
“…There are various histologic types of breast cancer that differ in microscopic appearance and receptor expression, leading to differences in response to the treatment. Recently, a multicentric study investigating the efficacy of electrochemotherapy in breast cancer patients with different receptor statuses was published ( 54 ). The study demonstrated that electrochemotherapy is equally effective in the treatment of breast cancer metastases, regardless of receptor status.…”
Section: Electrochemotherapy In Clinical Practicementioning
confidence: 99%
“…The response and local tumor control were better in multiple smaller lesions than in larger lesions, as previously observed. Local progression-free survival was, however, significantly lower in triple-negative type, probably due to the more aggressive cancer type and smaller choice of systemic treatments ( 54 ).…”
Section: Electrochemotherapy In Clinical Practicementioning
confidence: 99%